2020
DOI: 10.1038/s41467-020-19804-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral extension and synchronization of microcombs in a single microresonator

Abstract: Broadband optical frequency combs are extremely versatile tools for precision spectroscopy, ultrafast ranging, as channel generators for telecom networks, and for many other metrology applications. Here, we demonstrate that the optical spectrum of a soliton microcomb generated in a microresonator can be extended by bichromatic pumping: one laser with a wavelength in the anomalous dispersion regime of the microresonator generates a bright soliton microcomb while another laser in the normal dispersion regime bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 41 publications
(65 reference statements)
0
47
0
Order By: Relevance
“…The use of an auxiliary pump enables straightforward access to soliton states, through an effective temperature compensation mechanism that bypasses the thermal bistability 27 29 . Moreover, simultaneous spectral broadening of the comb, attributed to cross-phase modulation (XPM) effects, has also recently been observed 30 , though the magnitude of the effect was limited. Here, we consider a dual-pumped system in a regime where much more significant spectral broadening is realized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of an auxiliary pump enables straightforward access to soliton states, through an effective temperature compensation mechanism that bypasses the thermal bistability 27 29 . Moreover, simultaneous spectral broadening of the comb, attributed to cross-phase modulation (XPM) effects, has also recently been observed 30 , though the magnitude of the effect was limited. Here, we consider a dual-pumped system in a regime where much more significant spectral broadening is realized.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and colleagues have recently realized a similar dual pumping configuration, in which an auxiliary laser at 1330 nm spectrally broadens a 1550 nm soliton microcomb down to wavelengths of around 1275 nm 30 , considerably increasing the bandwidth of such low repetition rate DKS solitons. The spectrum extends from 1275 to 1720 nm (taken at the −50 dB points relative to the maximum), an extent of 60 THz, and the auxiliary laser is responsible for about 22 THz of spectral extension on the high frequency side, resulting in about a factor 1.5 × increase of the bandwidth of the comb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5a, there are four new frequencies beside the two pumps, based on the cascaded FWM. The OPO spectrum is expected to be symmetric, as shown in Figure 5b, which is simulated based on the Lugiato-Lefever equation using the same conditions as in the experiment [45]…”
Section: Dual-pump Opomentioning
confidence: 99%
“…On the other hand, in [29] a fraction of the soliton light generated in a first resonator was injected into a second resonator, and a soliton with identical repetition rate than the one in the master resonator could still be generated, even when their FSRs were dissimilar by up to ~8 MHz. In [30] a micro-resonator was pumped with two pumps 220nm apart, to generate solitons that had their repetition rate synchronized thanks to cross-phase modulation (XPM), even when pumping different mode families with dissimilar dispersion values. It has also been reported that modulating a pump with a 20 MHz signal resulted in the generation of soliton molecules with different constituent intensities, but with their repetition rates locked via XPM [31].…”
Section: Introductionmentioning
confidence: 99%